Neurocognitive Rehabilitation in Parkinson’s Disease with Motor Imagery: A Rehabilitative Experience in a Case Report - Federico Zangrando; Giulia Piccinini; Andrea Pelliccioni; Vincenzo Maria Saraceni; Teresa Paolucci (Case Reports in Medicine)
A 50-year-old female with Parkinson’s disease underwent a neurocognitive rehabilitation program consisting of one-hour-lasting sessions attended twice a week for three months. The balance and the risk of falls were determined using the Tinetti Balance and Gait Evaluation Scale. The pain was determined using the Visual Analog Scale and the course of the disease was examined using the Unified Parkinson’s Disease Rating Scale (UPDRS). Endpoints were before the treatment, at the end of the treatment, and at a 12-week follow-up. The aim of this study is to evaluate the efficacy of neurocognitive rehabilitation in PD with motor imagery. Primary outcome is the improvement in balance and the falls risk reduction; secondary outcome is lower limb pain reduction.